Russian National Registry of acute coronary syndrome: present state and perspectives - S. A. Boytsov; I. S. Yavelov; S. A. Shalnova; S. S. Yakushin; R. A. Liferov; N. N. Nikulina (Кардиоваскулярная терапия и профилактика, 2007)
In Russia, high cardiovascular mortality and absence of national epidemiological data on acute coronary syndrome (ACS) prevalence, lethality, and prognosis justify the development of the National ACS Registry, containing information on ACS incidence, lethality, mortality, healthcare quality, and facilitating further healthcare system improvement. This united national database will include the following information: in-hospital and out-patient treatment of ACS individuals; extra-healthcare service ACS mortality registration (“extra-service cases”); primary diagnostics of Q-wave as a sign of non-registered Q-wave myocardial infarction in anamnesis.